Improving Scientific Literacy in Primary Schools Using Experimental Methods - Wele, Maria Ancelina; Lawe, Yosefina Uge; Suparmi, Ni Wayan; Dinatha, Ngurah Mahendra (research, training and philanthropy institution Natural Aceh, 2024)
The research aims to increase scientific literacy in science learning using experimental learning methods, especially magnetic material in class IV SDK BOBA. The type of research used in this research is classroom action research where the research subjects are class IV students at SDK BOBA. This research was carried out in two cycles with the research stages used including planning, implementation, observation, and reflection stages. The research results showed that through the experimental method to increase students' scientific literacy in aspects of science as a body in cycle 1, it was 37.5% with very poor criteria. In contrast, in cycle 2, the percentage was 56.5%, with poor criteria and an increase of 19%. The percentage of the science aspect as a way to investigate in cycle 1 was 56.25% with poor criteria, while in cycle 2, the percentage was 75% with good criteria and increased by 18.75%. The percentage of the science aspect as a way of thinking in cycle 1 was 37.5% with very poor criteria, while in cycle 2, the percentage was 75% with good criteria and an increase of 37.5%. The percentage in the science aspect of the interaction between science, technology, and society in cycle 1 was 56.25% with poor criteria. In contrast, in cycle 2, the percentage was 75% with good criteria and increased by 18.5%. By using this method, students can develop critical thinking skills because, through this, students can experience an experimental process that begins with observing, analyzing, and then concluding.